An Investigation into the Link between English Teachers’ Classroom Management and English Achievement at one Islamic Senior High School - Melati Adela (Ta'dib: Jurnal Pendidikan Islam, 2020)
This study investigated the link between each dimension of English teachers’ classroom management and the twelfth grade students’ English achievement, and the influence of each dimension of English teachers’ classroom management on the twelfth grade students’ English achievement of one Islamic senior high school in Palembang. The correlation research design was applied in this study. The population of this study was the twelfth grade students. Convenience sampling technique was used to select the sample consisting of 85 students, 42 students of science class and 43 students of social class. The result analysis indicated that there was no significant correlation between behavioral dimension of classroom management and English achievement since the r-obtained (-.012) was lower than r-table (.213). Then, there was no significant correlation between instructional dimension of classroom management and English achievement since the r-obtained (-.016) was lower than r-table (.213). From the findings, it can be concluded that each dimensions of classroom management had no correlation with English achievement. It means that the English teachers’ classroom management was not a dominant factor affecting students’ English achievement.